Proceso de atención de enfermería en gestante de 33 semanas con preeclampsia. - Martillo Coello, Nancy Felicita (2022)
In Ecuador, preeclampsia is one of the pathologies with the highest morbidity rate in pregnant women, so that reference has been taken to carry out this clinical case. In the following clinical case we will deal with a pregnant woman of 33 weeks with a diagnosis of Preeclampsia, where the investigation was carried out at the IESS Quevedo Hospital in the Gynecology area. We use data collection methods to provide a better service during your hospital stay. We define preeclampsia as a pathology that appears in pregnant women after 20 weeks, showing warning signs such as edema, headaches, high blood pressure, there are women who fail to detect these symptoms, putting their life and that of the fetus at risk. It is important that during pregnancy they have monthly controls so that these pathologies can be detected and treated in time.